Role of Different Growth Enhancers as Alternative to In-feed Antibiotics in Poultry Industry - Rafiq, Kazi; Tofazzal Hossain, Muhammad; Ahmed, Rokeya; Hasan, Md. Mehedi; Islam, Rejaul; Hossen, Md. Ismail; Shaha, Sourendra Nath; Islam, Mohammad Rafiqul (Frontiers in Veterinary Science, 2022)
Poultry industry has grown so fast alongside an irrational use of antibiotics to maximize profit and make it cost effective production during last few decades. The rising and indiscriminate use of antibiotics might result in deposition of residues in poultry food products and to develop resistance to these drugs by the microorganisms, therefore many diseases are becoming difficult to treat both in humans and animal. In addition, use of low dose antibiotics as growth enhancer resulting antibiotic residues in food products having detrimental effects on human health. On the other hand, many studies have shown that antibiotics administered to poultry and livestock are poorly absorbed through gut and usually excreted without metabolism. These excreted antibiotics eventually accumulated in the environment and enter into human food chain resulting bioaccumulation of drugs residues in human body. In this regards to find out the alternatives are paramount important for the production of safe meat and egg. Therefore, in recent years much research attention were disarticulated towards the exploration for alternatives to antibiotic as in-feed growth enhancers after banding of the antibiotic growth enhancers by the EU. As a result, probiotics, prebiotics, phytobiotics, spirulina, synbiotic and their combination are being used more frequently in poultry production. Feed additives therefore gained popularity in poultry production having many advantages without any resides in poultry products. In addition, numerous studies have been conducted to demonstrate such biological supplements to compete with antimicrobial resistance. Therefore, the purpose of this review article was to highlight the advantages of using biological products instead of antibiotics as poultry in-feed growth enhancers to enhance production performance, reduce intestinal pathogenic bacteria and maintain gut health, potentiate the immune response, safety and wholesomeness of meat & eggs as evidence of consumer protection as well as improve the safety of poultry products for human consumption.